Competition Is the Underlying Mechanism Controlling Viscous Fingering and Wormhole Growth - Yoar Cabeza; Juan J. Hidalgo; Jesus Carrera (Geophysical Research Letters)
Abstract Viscous fingering and wormhole growth are complex nonlinear unstable phenomena. We view both as the result of competition for water in which the capacity of an instability to grow depends on its ability to carry water. We derive empirical solutions to quantify the finger/wormhole flow rate in single‐, two‐, and multiple‐finger systems. We use these solutions to show that fingering and wormhole patterns are a deterministic result of competition. For wormhole growth, controlled by dissolution, we solve reactive transport analytically within each wormhole to compute dissolution at the wormhole walls and tip. The generated patterns (both for viscous fingering and wormhole growth under moderate Damköhler number values) follow a power law decay of the number of fingers/wormholes with depth with an exponent of −1 consistent with field observations.